Systematic Review: Teknologi Needle Free Jet Injection Insulin (NFJI) Efektif Mengontrol Konsentrasi Glukosa Pada Penderita Diabetes Melitus Tipe 2 - Syahrizal, Rofi; Bakar, Abu; Harmayetty, Harmayetty; Puspita Sari, Anna Juwita (Universitas Tribhuwana Tunggadewi, 2023)
Needle-free jet injection (NFJI) is a needleless method for insulin delivery in type 2 diabetes mellitus (T2DM) patients. This study evaluates NFJI's effectiveness in controlling blood glucose. In this study, we conducted a systematic review following the PRISMA guidelines, searching six databases (EBSCO Host, ProQuest, PubMed, ScienceDirect, Scopus, and Web of Science). The search yielded a total of 379 articles. We used the following keywords: